2017
DOI: 10.1016/j.scriptamat.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Serrated flow in nanostructured binary Mg-Al alloys

Abstract: Serrated flow, also known as the Portevin-Le Chatelier effect, has been extensively investigated in binary Mg-alloys such as Mg-Ag, Mg-Y and Mg-Li alloys. Interestingly, however, this effect has not been observed in Mg-Al alloys. In this work, we report the appearance of serrations in nanostructured Mg-Al alloys processed by cryomilling and spark-plasma-sintering during in-situ SEM microcompression tests at room temperature and strain rates between 2 × 10 −3 and 10. The observed serrated stress-strain behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Mg-Al alloys [42]. The results indicate that thermal activation helps overcome the pinning of the dislocations by the solute atoms in Mg-9 at.%Al and Mg-Zn, so that after the initial elastic loading, yielding takes place smoothly by the gliding of pre-existing Supplementary Fig.…”
Section: Mechanical Response At 373k (100ºc)mentioning
confidence: 88%
“…Mg-Al alloys [42]. The results indicate that thermal activation helps overcome the pinning of the dislocations by the solute atoms in Mg-9 at.%Al and Mg-Zn, so that after the initial elastic loading, yielding takes place smoothly by the gliding of pre-existing Supplementary Fig.…”
Section: Mechanical Response At 373k (100ºc)mentioning
confidence: 88%
“…The process of auto-tuning of a certain channel is served to accomplish the test with accurate results and control performance. Although the system was being stable during the tests, many researchers have reported the serrated flow in some materials under a certain strain rate and temperature range [7][8][9][10][11]. It was considered as the material property rather than the noise of machine 2 of 9 system, commonly referred to as the Portevin-Le Chatelier (PLC) effect in numerous papers and books, e.g., [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The PLC effect has been investigated by stress and strain-controlled tensile tests as well as digital image correlation and acoustic emission [21]. Recently some researchers have reported the PLC effect under compressive loading as well [9].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the former, Amokhtar et al [23] investigated the evolution of serration morphology with different Mg contents and applied strain rates. Moreover, Pozuelo et al [24] studied the stress drop magnitude in nanostructured binary Mg-Al alloys and discovered that it follows a linear relationship with the number of stress drops. Sarkar et al [25] compared the stress drop magnitude in HT-9 steel at different temperatures, and the experimental results indicated that it is enlarged by increasing temperature.…”
Section: Introductionmentioning
confidence: 99%